2015
DOI: 10.1016/j.micres.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of endophytic fungus, Guignardia mangiferae for extracellular synthesis of silver nanoparticles and their in vitro biological activities

Abstract: The aim of this study was to synthesize highly biocompatible and functionalized silver nanoparticles using endophytic fungi isolated from the leaves of medicinal plants. Among 13 fungi tested, the isolate, Guignardia mangiferae (Bios PTK 4) extracellularly synthesized well-dispersed and extremely stable silver nanoparticles under optimized reaction conditions within 12 h. These nanoparticles were characterized by HR-TEM, SAED, XRD and EDX analyses. G. mangiferae synthesized 5-30 nm sized, spherical shaped silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(83 citation statements)
references
References 32 publications
3
77
1
2
Order By: Relevance
“…6 and Table 2 test concentration of 1 mg/ mL. The zone of inhibition exhibited by silver nanoparticles was found to be higher than our previous study (Balakumaran et al, 2015) and slightly lower than those reported by Elbeshehy et al (2015). The highest antimicrobial activity was recorded against Gram-negative bacteria and this result was in good agreement with the earlier studies (Balakumaran et al, 2015;Elbeshehy et al, 2015).…”
Section: Well Diffusion Assaysupporting
confidence: 90%
See 2 more Smart Citations
“…6 and Table 2 test concentration of 1 mg/ mL. The zone of inhibition exhibited by silver nanoparticles was found to be higher than our previous study (Balakumaran et al, 2015) and slightly lower than those reported by Elbeshehy et al (2015). The highest antimicrobial activity was recorded against Gram-negative bacteria and this result was in good agreement with the earlier studies (Balakumaran et al, 2015;Elbeshehy et al, 2015).…”
Section: Well Diffusion Assaysupporting
confidence: 90%
“…Similarly, no change in the peak at 535 nm was also noticed for gold nanoparticles. However, the peaks for silver and gold nanoparticles got shifted during the course of third month but in both cases, there was no sign of aggregation of nanoparticles observed (Balakumaran, 2015). On the contrary, Bacillus spp.…”
Section: Characterization Of Silver and Gold Nanoparticlesmentioning
confidence: 91%
See 1 more Smart Citation
“…There are many previous studies connected the stability and antibacterial activity of Ag NPs bio-fabricated from different endophytic fungi with pH and reported the optimum pH was 76390, pH 5428091 and pH 3 reported by9293949596. Finally6297 recorded that biosynthesis of Ag NPs by using extracellular fraction of Trichoderma reesei and T. harzianum without adjusting pH and reported the formation of polydisperse spherical and occasionally ellipsoid Ag NPs in the size range from 5–63 nm at room temperature started within 3 hr.…”
Section: Discussionmentioning
confidence: 99%
“…(9.37 mm). 259 In another study, AgNO 3 was tested against three fungi namely Trichoderma spp. (ATCC 18648), Mucor spp.…”
mentioning
confidence: 99%